Post-operative results of tricuspid annuloplasty with teflon felt - Surabhi, P. Sai; Tadiboina, Avinash; Kumar, R. V.; Dev, Tella Ramakrishna (International Journal of Research in Medical Sciences, 2021)
Background: Surgical treatment of functional tricuspid valve regurgitation (TR) with left-sided valvular disease still remains a challenge for the cardiac surgeon. We present our observations and results on the usage of Teflon felt as an economic and easily available option for the management for tricuspid disease with an emphasis on the ease of procedure. Methods: In this study 50 (27 male and 23 female) adult skulls were investigated to determine the type of asterion, its distance from important bony landmarks and also the nearby venous sinuses were measured. Results: Epidemiological data like age, gender, symptomatic status using NYHA class, intraoperative details including the procedure performed, cardiopulmonary bypass and cross clamp time were noted. Patients’ preoperative echocardiograms, postoperative echocardiograms done at 1 month, 3 month and 6 month and yearly follow ups were made note of. Most of the patients in our study group are in 4th decade of life with slight female preponderance. Tricuspid regurgitation secondary to rheumatic valvular disease involving left sided valves is the most common etiology. The average size of the teflon felt was sized to the standard SJM sizer and sized to 28.56±3.7 mm. The average CPB time is 138 min 19 sec and average cross clamp time 89 min 14 sec. Five patients had postoperative RV dysfunction out of which three patients recovered with medical management. Overall in-hospital mortality in our study group is 6 (8%). 3 of them died due to low cardiac output, two patients due to sepsis and MODS and one due to bleeding. Conclusions: Annuloplasty with customised hard teflon felt is a safe, easily reproducible, economic alternative with good results and less mortality and morbidity.